2015
DOI: 10.7554/elife.07423
|View full text |Cite
|
Sign up to set email alerts
|

Social communication of predator-induced changes in Drosophila behavior and germ line physiology

Abstract: Behavioral adaptation to environmental threats and subsequent social transmission of adaptive behavior has evolutionary implications. In Drosophila, exposure to parasitoid wasps leads to a sharp decline in oviposition. We show that exposure to predator elicits both an acute and learned oviposition depression, mediated through the visual system. However, long-term persistence of oviposition depression after predator removal requires neuronal signaling functions, a functional mushroom body, and neurally driven a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
150
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(161 citation statements)
references
References 59 publications
9
150
0
2
Order By: Relevance
“…For example, fruit fly ( Drosophila sp.) and ladybird beetle (Adalia bipunctata) females altered timing of egg laying and total egg number under conditions of simulated predation risk . Similarly, we found that female Q‐flies laid fewer eggs when predators were present.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…For example, fruit fly ( Drosophila sp.) and ladybird beetle (Adalia bipunctata) females altered timing of egg laying and total egg number under conditions of simulated predation risk . Similarly, we found that female Q‐flies laid fewer eggs when predators were present.…”
Section: Discussionmentioning
confidence: 54%
“…The presence of predators is known to influence the egg‐laying behaviour of a number of prey species . For example, fruit fly ( Drosophila sp.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Kacsoh et al . () found that Drosophila can use a simple visual cue to initiate programmed cell death within the ovary of another fly. We found that honey bee workers exposed to queen pheromone have a higher level of caspase activity in the ovary compared with non‐exposed workers.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that the social environment of an organism, signalled via a pheromone, can influence programmed cell death within a specific tissue. Interestingly, Kacsoh et al (2015) found that Drosophila can use a simple visual cue to initiate programmed cell death within the ovary of another fly. We found that honey bee workers exposed to queen pheromone have a higher level of caspase activity in the ovary compared with nonexposed workers.…”
Section: Discussionmentioning
confidence: 99%